Reservoirs of Listeria Species in Three Environmental Ecosystems - Linke, Kristina (American Society for Microbiology, 2014)
Soil and water are suggested to represent pivotal niches for the transmission of Listeria monocytogenes to plant material, animals, and the food chain. In the present study, 467 soil and 68 water samples were collected in 12 distinct geological and ecological sites in Austria from 2007 to 2009. Listeria was present in 30% and 26% of the investigated soil and water samples, respectively. Generally, the most dominant species in soil and water samples were Listeria seeligeri, L. innocua, and L. ivanovii. The human- and animal-pathogenic L. monocytogenes was isolated exclusively from 6% soil samples in regions A (mountainous region) and B (meadow). Distinct ecological preferences were observed for L. seeligeri and L. ivanovii, which were more often isolated from wildlife reserve region C (Lake Neusiedl) and from sites in proximity to wild and domestic ruminants (region A). The higher L. monocytogenes detection and antibiotic resistance rates in regions A and B could be explained by the proximity to agricultural land and urban environment. L. monocytogenes multilocus sequence typing corroborated this evidence since sequence type 37 (ST37), ST91, ST101, and ST517 were repeatedly isolated from regions A and B over several months. A higher L. monocytogenes detection and strain variability was observed during flooding of the river Schwarza (region A) and Danube (region B) in September 2007, indicating dispersion via watercourses.